Regional simulations of equatorial spread F driven with, and an analysis of, WAM-IPE electric fields - Kirchman, Aaron; Hysell, David; Fang, Tzu-Wei (Frontiers in Physics, 2025)
A three-dimensional, regional simulation is used to investigate ionospheric plasma density irregularities associated with Equatorial Spread F. This simulation is first driven with background electric fields derived from ISR observations. Next, the simulation is driven with electric fields taken from the WAM-IPE global model. The discrepancies between the two electric fields, particularly in the evening prereversal enhancement, produce disagreeing simulation results. The WAM-IPE electric fields are then studied through a simple sensitivity analysis of a field-line integrated electrodynamics model similar to the one used in WAM-IPE. This analysis suggests there is no simple tuning of ion composition or neutral winds that accurately reproduce ISR-observed electric fields on a day-to-day basis. Additionally, the persistency of the prereversal enhancement structure over time is studied and compared to measurements from the ICON satellite. These results suggest that WAM-IPE electric fields generally have a shorter and more variable correlation time than those measured by ICON.